Práctica de la medicina ancestral en las mujeres embarazadas atendidas en el área de consulta externa del hospital provincial general Julius Doepfner del cantón Zamora. año 2015 - Chamba Zhindón, Shirley Dayana (2016)
The purpose of this investigation was determined by the practice of Ancestral Medicine on the pregnant women attended in the external consultant area of the Julius Doepfner Hospital of Zamora city. Year 2015, the kind of investigation was descriptive, prospective, transversal and of field, it’s been applied the technique of survey, taking as implement the questionnaire applied to a sample of 50 pregnants, getting the following results: in the age, women between 19-30 years old have predominated with 62%, 58 % have approved the high school level, 78% live in the urban zone, 41% are from mixed ethnicity, the medium economic level has predominated with 90%, it’s been exposed too that 92% of the pregnants have had the traditions or habits of going to midwifes to: reposition the baby with 64%, take sitz bath have participated a 66%, and put on oils have participated a 10%, the same way to use natural plants during the pregnant it has been noticed that a 84% of the pregnants have concurred to this practice, consuming concoctions based on basil, schnapps and panela with a 40%, as the cinnamon with a 40%, later it’s been detected complications on the pregnants due to the use of natural products being this the anxiety with a 42% and the excessive hip pain with 34%. Finally we conclude that involved perform several types of traditional practices in their pregnancy as concoctions with 84 % and sitz baths with 66% . Considering the results the author executed an interventional plan based on an educational program through educational conferences, explanation workshops, along with a radio programming through a publicity spot, in order to inform to the community.